A systematic mapping of social entrepreneurship orientation: A call for increased collaboration and future research agenda - Lestari, Yogi Dwi; R.W.W., Ery Tri Djatmika; Sopiah, Sopiah; Handayati, Puji; Firdiansyah, Yhadi (Edelweiss Applied Science and Technology, 2026)
This study aims to systematically map and synthesize the development of Social Entrepreneurship Orientation (SEO) research and to identify future research directions. It employs a Systematic Literature Review (SLR) combined with bibliometric analysis. Data were collected from the Scopus database using the keyword “Social Entrepreneurship Orientation” in the title, abstract, and keywords fields. A total of 1,174 publications (2017–2025) were identified and analyzed using VOSviewer to examine publication trends, collaboration networks, and thematic structures. SEO research remains in an emerging, fragmented stage despite a rising trend in publications. Research is focused on a few countries and institutions, with limited international collaboration. The analysis highlights that SEO is closely linked to performance outcomes, while contextual, institutional, and innovation-related aspects remain underexplored. SEO research is still developing and requires more integrated, cross-national, and longitudinal studies to enhance theoretical development and empirical validation. The findings provide valuable insights for researchers, practitioners, and policymakers to develop collaborative and context-aware strategies for advancing social entrepreneurship practices. This study offers a thorough bibliometric analysis and highlights key gaps to inform future SEO research.